2023
DOI: 10.1186/s12915-023-01511-7
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti exhibits a distinctive mode of late ovarian development

Abstract: Background Insects live in almost every habitat on earth. To adapt to their diverse environments, insects have developed a myriad of different strategies for reproduction reflected in diverse anatomical and behavioral features that the reproductive systems of females exhibit. Yet, ovarian development remains largely uncharacterized in most species except Drosophila melanogaster (D. melanogaster), a high Diptera model. In this study, we investigated the detailed developmental process of the ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The formation of Aedes ovariole, similar to that of Drosophila melanogaster , begins in the late larval stage [ 39 ]. In control pupae, the pre-ovarioles (defined as the immature form of ovariole) formed and resided on the surface of the ovary (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of Aedes ovariole, similar to that of Drosophila melanogaster , begins in the late larval stage [ 39 ]. In control pupae, the pre-ovarioles (defined as the immature form of ovariole) formed and resided on the surface of the ovary (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Third, our previous study on Ae. aegypti germline development revealed that the late pupal stage represents the crucial phase for the maturation of ovaries [ 39 ]. These findings establish an optimal window for using irradiation to target the female germline for sterilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ae. aegypti , follicles in the ovaries containing oocytes are kept in a previtellogenic state until a blood meal is imbibed ( 38 ). Upon blood feeding the ovaries take up proteins and fats from the haemolymph, originating mainly from the fat body, to produce mature oocytes ( 37 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Aedes albopictus (NEA-EHI strain) was obtained from the National Environment Agency (NEA), Singapore. The colony was maintained in the insectary as described previously [ 26 ]. Mosquitoes were infected with CHIKV-BP or CHIKV-SP using a Hemotek membrane feeding system as described earlier [ 27 ].…”
Section: Methodsmentioning
confidence: 99%